บทสะท้อนแนวคิดว่าด้วยชุดการสอน ชุดกิจกรรมการเรียนรู้ และชุดการเรียนรู้ - (Wichian Thamrongsotthisakul), วิเชียร ธำรงโสตถิสกุล (Journal of Education and Innovation, 2017)
ชุดการสอนเป็นนวัตกรรมทางการศึกษาที่ ศาสตราจารย์ ดร.ชัยยงค์ พรหมวงศ์ ได้พัฒนาขึ้นตามระบบการสอนแบบศูนย์การเรียนโดยใช้ชุดการสอนสื่อประสมแผนจุฬา เมื่อ พ.ศ. 2516 เพื่อทดลองใช้กับนิสิตปริญญาโทที่เรียนรายวิชา “เทคโนโลยีกับการศึกษาร่วมสมัย” ที่แผนกวิชาโสตทัศนศึกษา คณะครุศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย ปัจจุบันชุดการสอนเป็นนวัตกรรมทางการศึกษาที่ครูนิยมนำมาใช้ในการจัดการเรียนการสอนและพัฒนาเพื่อทำเป็นผลงานทางวิชาการอย่างแพร่หลายในทุกระดับชั้นเรียน รวมทั้งได้รับความนิยมในการนำชุดการสอนมาพัฒนาเป็นหัวข้อวิทยานิพนธ์และการศึกษาค้นคว้าอิสระของนิสิตนักศึกษาระดับปริญญาโท โดยเฉพาะในสาขาหลักสูตรและการสอน มีงานวิจัยจำนวนมากได้ตั้งชื่อและกำหนดนิยามของชุดการสอนขึ้นมาใหม่อย่างสับสนปะปนกัน บทความนี้จึงนำเสนอความคิดว่าด้วยชุดการสอน ชุดกิจกรรมการเรียนรู้ และชุดการเรียนรู้ ในประเด็นที่เกี่ยวกับความหมาย ลักษณะ และคุณค่าของชุดการสอน รวมถึงหลักการเรียนรู้ และทฤษฎีการเรียนรู้ที่นำไปสู่การสร้างและใช้ชุดการสอน การนำเสนอแนวคิดดังกล่าวนี้เพื่อเป็นหลักคิดสำหรับนักวิชาการด้านหลักสูตรและการสอน นักการศึกษา ครู อาจารย์ และผู้ใช้ชุดการสอนให้หันกลับมาพิจารณาว่า จากแรกเริ่มชุดการสอน แปลงเปลี่ยนเป็นชุดกิจกรรมการเรียนรู้ และชุดการเรียนรู้นั้น มีพัฒนาการทั้งในแง่ของความหมาย ลักษณะ และคุณค่า รวมถึงหลักการเรียนรู้ และทฤษฎีการเรียนรู้ที่นำไปสู่การสร้างและใช้ที่แตกต่างกัน THE REFLECTION ON THE CONCEPTS OF INSTRUCTIONAL PACKAGE, LEARNING ACTIVITY PACKAGE AND LEARNING PACKAGE An instructional package is an educational innovation that was developed by Prof. Dr. Chaiyong Brahmawong through instructional system for Learning-Center Classroom using “Chula Plan” multi-media instructional packages in B.E. 2516. This instructional package was tried out with master degree students who enrolled in “Technology and Contemporary Education” at Department of Audio Visual Education, Faculty of Education, Chulalongkorn University. Now, the concept of an instructional package is widely used among teachers in their teaching and creating academic works in every grade level. This concept is also commonly employed in research in the form of thesis or independent study of master degree students in curriculum and instruction program. Due to the broad application of the concept, the name and the definition of the instructional package were defined differently by many researchers and this caused the confusion among educators. This article aimed at presenting the concepts of an instructional package, a learning activity package, and a learning package in the term of its meanings, characteristics, and values. In addition, the learning principles and learning theories for developing and using an instructional package are also discussed. This article was written for academics in curriculum and instruction field, educators, teachers, and instructional package users in order to provide the consideration about the development of an instructional package, a learning package, and a learning activity package focusing on its meaning, characteristics, values, and learning principles and theories that are used for different purposes.